European guideline on obesity care in patients with gastrointestinal and liver diseases- Joint ESPEN/UEG guideline - KANİ, HALUK TARIK (My University, 2022)
Background: Patients with chronic gastrointestinal (GI) disease such as inflammatory bowel disease (IBD), irritable bowel syndrome (IBS), celiac disease, gastroesophageal reflux disease (GERD), pancrea-titis, and chronic liver disease (CLD) often suffer from obesity because of coincidence (IBD, IBS, celiac disease) or related pathophysiology (GERD, pancreatitis and CLD). It is unclear if such patients need a particular diagnostic and treatment that differs from the needs of lean GI patients. The present guideline addresses this question according to current knowledge and evidence.Objective: The objective of the guideline is to give advice to all professionals working in the field of gastroenterology care including physicians, surgeons, dietitians and others how to handle patients with GI disease and obesity.Methods: The present guideline was developed according to the standard operating procedure for ESPEN guidelines, following the Scottish Intercollegiate Guidelines Network (SIGN) grading system (A, B, 0, and good practice point (GPP)). The procedure included an online voting (Delphi) and a final consensus conference.Results: In 100 recommendations (3x A, 33x B, 24x 0, 40x GPP, all with a consensus grade of 90% or more) care of GI patients with obesity -including sarcopenic obesity -is addressed in a multidisciplinary way. A particular emphasis is on CLD, especially fatty liver disease, since such diseases are closely related to obesity, whereas liver cirrhosis is rather associated with sarcopenic obesity. A special chapter is dedi-cated to obesity care in patients undergoing bariatric surgery. The guideline focuses on adults, not on children, for whom data are scarce. Whether some of the recommendations apply to children must be left to the judgment of the experienced pediatrician.Conclusion: The present guideline offers for the first time evidence-based advice how to care for patients with chronic GI diseases and concomitant obesity, an increasingly frequent constellation in clinical practice.(c) 2022 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Beslenme ve Dietetik; Tarımsal Bilimler; Ziraat; Sağlık Bilimleri; Nutrition and Dietetics; Agricultural Sciences; Agriculture; Health Sciences; BESLENME VE DİYETETİK; Tarım Bilimleri; Tarım ve Çevre Bilimleri (AGE); NUTRITION & DIETETICS; AGRICULTURAL SCIENCES; Agriculture & Environment Sciences (AGE); Beslenme ve Diyetetik; Obesity; Sarcopenic obesity; Inflammatory bowel disease; Non-alcoholic fatty liver disease; Bariatric surgery; NONALCOHOLIC FATTY LIVER; INFLAMMATORY-BOWEL-DISEASE; BODY-MASS INDEX; GASTROESOPHAGEAL-REFLUX DISEASE; Y GASTRIC BYPASS; CONTROLLED ATTENUATION PARAMETER; EXOCRINE PANCREATIC INSUFFICIENCY; CLINICAL-PRACTICE GUIDELINES; POST-BARIATRIC SURGERY; LIFE-STYLE INTERVENTION